One Roof Integrated Six-Year Secondary High School in Indonesia: A Proposal for Efficiency and Quality Improvement - Abdullah A Afifi; Mona Eliza; Nor Anisa Arifin (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
Indonesia’s secondary education system is currently divided into two distinct stages: junior and senior high school. While this structure aligns with traditional education policy frameworks, it has shown inefficiency in addressing Indonesia’s education vision, geographic diversity, resource limitations, and quality disparities, particularly in rural and remote areas. This article proposes the integration into a unified six-year secondary school model as a solution to systemic inefficiencies and quality concerns. By analyzing educational statistics, policy documents, and international best practices, this paper outlines the potential of integrated secondary schools to reduce operational fragmentation, optimize teacher deployment, and strengthen curriculum continuity. Drawing from a qualitative document analysis approach, the article references data from the government records and relevant international practices from other countries. The articles also provide the case study made in Perguruan Darulfunun Payakumbuh. The discussion highlights how school mergers can maximize infrastructure utilization, reduce student retention, optimize teacher allocation, relieve costs, and enrich student learning. Key challenges identified include legal and administrative adjustments, resistance from local stakeholders, and the need for professional teacher realignment. This integrated model aligns with the national compulsory education mandate, ensuring a smoother transition between lower and upper secondary education. The article concludes by recommending phased policy reform and pilot programs to explore the feasibility and scalability in diverse regional contexts across Indonesia.